THE LOCALIZATION OF SPECTRIN ON THE INNER SURFACE OF HUMAN RED BLOOD CELL MEMBRANES BY FERRITIN-CONJUGATED ANTIBODIES - Nicolson, Garth L. (The Rockefeller University Press, 1971)
Spectrin, a major protein constituent of mammalian red blood cell membrane preparations, has been localized on the inner surface of human red blood cell membranes by techniques that utilized specific ferritin-conjugated antibodies and fixation of membranes shortly after hemolysis so as to allow penetration of the ferritin-antibody labels. The labeling of spectrin was shown to be specific by the following criteria. (a) Nonhomologous ferritin-conjugated antibodies did not specifically bind to either membrane surface. (b) Blocking the membrane-bound spectrin with excess unconjugated antispectrin antibodies prevented ferritin-antibody labeling. (c) Removal of spectrin by treating the membrane preparation with a low ionic strength buffer containing ethylenediaminetetraacetate and β-mercaptoethanol prevented labeling by specific ferritin-conjugated antibodies.